2003
DOI: 10.1046/j.1464-410x.2003.04023.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotoresect for bloodless transurethral resection of the prostate: a 4‐year follow‐up

Abstract: OBJECTIVE To report the results and long‐term follow‐up of transurethral resection of the prostate (TURP) with a new resection device, the Rotoresect (Karl Storz, Tuttlingen, Germany). PATIENTS AND METHODS Most endoscopic resection techniques for benign prostatic tissue aim for high ablation rates and minimal bleeding. Available resection electrodes are effective, but cause high blood loss (loop electrode), or less bleeding but poorer ablation rates (electrovaporization). To resolve these conflicts the Rotores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Roller bars vaporize the prostate with their grooved surface by direct application of a high temperature to the tissue, similar to that obtained with a laser. The rotoresect electrode represents another variety; an axial rotating resection electrode, driven by a micromotor, and application of high‐frequency current simultaneously enables coagulation, vaporization and mechanical tissue removal during resection [4].…”
Section: Variation Of the Resection Loopmentioning
confidence: 99%
“…Roller bars vaporize the prostate with their grooved surface by direct application of a high temperature to the tissue, similar to that obtained with a laser. The rotoresect electrode represents another variety; an axial rotating resection electrode, driven by a micromotor, and application of high‐frequency current simultaneously enables coagulation, vaporization and mechanical tissue removal during resection [4].…”
Section: Variation Of the Resection Loopmentioning
confidence: 99%
“…Surgical treatment can fundamentally relieve clinical symptoms by removing part of the hyperplastic glands, especially the transurethral resection of the prostate which effectively treats BPH. However, surgery still has limitations, such as inducing adverse reactions (prostate resection syndrome, bleeding, postoperative urinary incontinence, and retrograde ejaculation) [ 24 26 ]. Rapid development of science and technology has witnessed emergence of new surgical methods for BPH, such as plasmakinetic resection [ 27 ], laser surgery [ 28 ], and enucleation surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Michel et al [14] in a porcine model; reported that the rate of tissue ablation with rotoresection was similar to that achieved by a standard resection loop, which is more than twice that obtained by conventional electrovaporization, and the rate of bleeding was much less than with standard loop resection. In a more recent report by Michel et al [15], 84 patients were followed up to 4 years. The number who completed the 4‐year follow‐up is not stated, but in those followed at 4 years, Q max continued to be significantly higher than before surgery (24.2 (8.2) vs 9.1 (4.9) mL/s).…”
Section: Discussionmentioning
confidence: 99%